2020
DOI: 10.1021/acs.jmedchem.0c00564
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-Walk Approach to Explore Bioisosteric Replacements in a Series of Potent A2B Adenosine Receptor Antagonists

Abstract: A systematic exploration of bioisosteric replacements for furan and thiophene cores in a series of potent A 2B AR antagonists has been carried out using the nitrogen-walk approach. A collection of 42 novel alkyl 4-substituted-2-methyl-1,4dihydrobenzo [4,5]imidazo[1,2-a]pyrimidine-3-carboxylates, which contain 18 different pentagonal heterocyclic frameworks at position 4, was synthesized and evaluated. This study enabled the identification of new ligands that combine remarkable affinity (K i < 30 nM) and exquis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 70 publications
2
50
0
Order By: Relevance
“…To experimentally validate this hypothesis, the ISAM-140 enantiomers were separated and their absolute configuration unequivocally assigned. Besides this goal, the enantiomeric separation and pharmacological characterization of this reference A 2B AR antagonist allowed to confirm the expected higher affinity of the S enantiomer, in line with the original modeling hypothesis 11 and recent similar results obtained with derivatives of this scaffold 10 , 13 , 14 .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…To experimentally validate this hypothesis, the ISAM-140 enantiomers were separated and their absolute configuration unequivocally assigned. Besides this goal, the enantiomeric separation and pharmacological characterization of this reference A 2B AR antagonist allowed to confirm the expected higher affinity of the S enantiomer, in line with the original modeling hypothesis 11 and recent similar results obtained with derivatives of this scaffold 10 , 13 , 14 .…”
Section: Discussionsupporting
confidence: 79%
“…1 ) 11 , 12 . The prediction of the active stereoisomer for this chemotype was later confirmed indirectly by experimental characterization of the active stereoisomers for representative compounds of a series of cyanopyrimidines 10 , fluorinated tricyclic derivatives 13 and aza-bioisosteres of the pentagonal heterocycle 14 . This binding model proposed that the stereospecific complementarity to the A 2B AR cavity was due to the optimal accommodation of the thiophene/furan ring around the chiral center of the core scaffold (Fig.…”
Section: Introductionmentioning
confidence: 88%
“…The investigated DHP derivatives were assembled in excellent yields by modification of the versatile and highly robust Biginelli reaction [2,3], a three-component transformation involving the catalysed condensation of a 1,3-dinucleophile (urea/thiourea or cyclic derivatives), and an aldehyde and β-ketoester [4]. A diverse series of DHP derivatives were explored [5][6][7][8][9][10][11] and optimal substituents in different positions of the heterocyclic core were identified as follows: (i) 2-or 3-furyl as well as 2-or 3-thienyl moiety at C4, (ii) ethyl or isopropyl ester group at C5, (iii) a methyl group at C6, and (iv) NH at position 1. Further diversification of the original 4-aryl-DHP scaffold [5,[12][13][14][15] produced new ligands with improved affinity and selectivity profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the enantioselective binding of racemic DHPs to A 2B AR, it was demonstrated that the receptor affinity is almost exclusively due to the (S)-enantiomer [6,[8][9][10][11]. The pharmacological evaluation of chiral DHP ligands investigated herein, 6, 7, and 13, resolved into their enantiomers by chiral HPLC with polysaccharide-based CSPs in NP mode, demonstrated highly enantioselective recognition at the A 2B AR binding site, with the eutomers (S) showing K i values in the low nanomolar range (6.30, 15.1, and 11.1 nM for 6, 7, and 13, respectively) and the distomers (R) achieving less than 25% inhibition in all cases [6,11].…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been developed by other groups using various catalysts and conditions. [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] In the rest of these works, we report a new consecutive four‐component reaction for the synthesis of 3,4‐dihydrobenzo[4,5]imidazo[1,2‐ a ]pyrimidin‐2(1 H )‐ones by successive addition of aniline, DMAD, benzaldehyde derivatives and 2‐aminobenzimidazole in the presence of new organic‐inorganic hybrid nanomagnetic catalyst in water/EtOH as a green solvent.…”
Section: Introductionmentioning
confidence: 99%